Effect of alloyed Sr on the microstructure and corrosion behavior of biodegradable Mg-Zn-Mn alloy in Hanks' solution. (15th August 2019) - Pan, Hui; Pang, Kun; Cui, Fengzhen; Ge, Feng; Man, Cheng; Wang, Xin; Cui, Zhongyu
Highlights: Sr promotes micro-galvanic corrosion and undermining of Mg17 Sr2 phases. Sr increases weight loss rate but inhibits localized corrosion of Mg-Zn-Mn alloy. Corrosion depth/second phase spacing keep constant as added Sr content exceeds 1.0 wt.%. The optimum Sr content is 1.0˜1.5 wt.% in Mg-1Zn-1 Mn alloy. Abstract: Effect of Sr on microstructure and corrosion behavior of biodegradable Mg-1Zn-1Mn- x Sr alloy is investigated. Decrease in second phase spacing and linear increase of Mg17 Sr2 fraction are observed with increasing Sr content. Corrosion rate increases linearly with increasing Sr content from 0 to 1.5 wt.% because of the enhanced micro-galvanic corrosion. Undermining of Mg17 Sr2 and α-Mg grains results in the dramatic increase in corrosion rate at a high Sr content (3.0 wt.%). Localized corrosion is inhibited by alloying with Sr, yielding an optimum Sr content of 1.0˜1.5 wt.% with comprehensive consideration of uniform/localized corrosion resistance and biomedical adaptability.